Penegakan Hukum Pidana Terhadap Kelalaian Pengemudi Kendaraan Bermotor yang Mengakibatkan Kecelakaan Lalu Lintas - Setiawan, Sulanjar Tri; Abadi, Suwarno; Aji, Rihantoro Bayu (Law and Humanity, 2024)
One of the traffic problems in Indonesia is the high number of road accidents caused by driver negligence. Therefore, law enforcement is one of the efforts to address the problem of road accidents. In current practice, traffic law enforcement does not only refer to criminal sanctions as in Law Number 22 Year 2009 on Road Traffic and Transport, but also uses restorative justice methods. This article discusses how the law is enforced in relation to traffic offences caused by the negligence of drivers who cause traffic accidents, and the obstacles in enforcing the law. This is legal research with statute and conceptual approach. The results revealed that law enforcement against negligence of motor vehicle drivers resulting in accidents is conducted with a repressive approach through restorative justice based on police discretionary authority granted through the Police Law. Specifically, the restorative justice approach is regulated through Regulation of the Chief of the Indonesian National Police Number 8 of 2021 concerning the handling of criminal acts based on restorative justice. However, its application is hindered by legal obstacles such as legal problem, law enforcers, citizen and culture. It is therefore necessary to enhance the capabilities and qualifications of law enforcement personnel in accordance with their respective areas of responsibility. This may be achieved through formal education or specialised training, with the objective of facilitating law enforcement through a restorative justice approach.